Math Fables lessons that count. - Tang, Greg (New York : Scholastic Press, 2004)
A series of rhymes about animals introduces counting and grouping numbers, as well as examples of such behaviors as cooperation, friendship, and appreciation.
This collection of whimsical math stories gives young kids a head start on the road to higher math. More than just another counting book, it begins building the foundation for arithmetic and problem solving by encouraging children to think about numbers in creative ways. Important adding and grouping concepts are introduced, together with light and cheerful lessons about life.
K-3
Keywords: Counting--Juvenile literature; Counting; Conduct of life